2015
DOI: 10.3389/fnhum.2015.00503
|View full text |Cite
|
Sign up to set email alerts
|

An engineered glove for investigating the neural correlates of finger movements using functional magnetic resonance imaging

Abstract: Objective measurement of concomitant finger motor performance is recommended for functional magnetic resonance imaging (fMRI) studies investigating brain activity during finger tapping tasks, because performance modality and ability can influence the selection of different neural networks. In this study, we present a novel glove system for quantitative evaluation of finger opposition movements during fMRI (called Glove Analyzer for fMRI, GAF). Several tests for magnetic resonance (MR) compatibility were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Bonzano and colleagues recently demonstrated that greater (motor) cortico-cerebellar connectivity (i.e. less inhibition) was correlated with learning on a finger-tapping task in PwMS (Bonzano et al, 2015). Conversely, recent work from our group found that while greater cortico-cerebellar connectivity strength was associated with better short-term postural adaptation in healthy young adults, this association was not observed in PwMS (r = 0.03) (Fling et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…Bonzano and colleagues recently demonstrated that greater (motor) cortico-cerebellar connectivity (i.e. less inhibition) was correlated with learning on a finger-tapping task in PwMS (Bonzano et al, 2015). Conversely, recent work from our group found that while greater cortico-cerebellar connectivity strength was associated with better short-term postural adaptation in healthy young adults, this association was not observed in PwMS (r = 0.03) (Fling et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…In details, five conducting metal sensors are located on the palmar surface of the distal phalanxes of the glove, like fingerprints, in order to record the contact during opposition movements between the thumb and another finger (detecting a square wave corresponding to contact/no contact) [ 8 , 10 ]. Data were acquired at 1 KHz by means of a data acquisition board (USB-1208FS, Measurement Computing, USA).…”
Section: Methodsmentioning
confidence: 99%
“…An ad hoc software tool generated the acoustic pacing signal, which was delivered by the system and listened by the subjects through isolation headphones, and recorded the occurrence of each tone and of each finger touch in the motor sequence. As previously reported, the program used to provide the cue and for data recording and analysis was developed with the Microsoft Visual Studio 2013,.NET Framework 4.5, written in C# exploiting the Windows Presentation Foundation for desktop application development platform [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…We were able to quantify both actual and mental performance concomitantly with fMRI acquisition by an ad hoc developed MR-compatible engineered glove 18 27 . Specifically, actual movements consisted in 5 repetitions of the sequence (thumb-to-index, medium, ring and little finger) and motor performance was assessed by the whole movement duration.…”
Section: Methodsmentioning
confidence: 99%
“…During each session, participants had to actually and mentally perform a simple sequence of finger opposition movements, as accurate and fast as possible. Simultaneous motor performance was measured by using a magnetic-resonance-compatible engineered glove 18 .…”
mentioning
confidence: 99%